Avaliação da resposta a prednisona no dia 8 da fase de indução do tratamento de leucemias linfoblástica aguda: enfoque na determinação do percentual de blastos residuais por citometria de fluxo e valor preditivo de prognóstico - SANTOS, Khalil Lima da Costa Maia dos (2020)
Introduction: Acute lymphoid leukemias (ALL) are the most common neoplasms in childhood, accounting for 25 to 30% of cases in the age group from 1 to 9 years. However, in adults it represents about 20%. It is characterized by the maturation block and proliferation of precursor cells of the lymphoid lineage after undergoing specific genetic-molecular changes. Patients are submitted to treatment protocols that determine how risk stratification: the response to prednisone on Day 8 (D8) of treatment, assessed by cytomorphology, minimal residual disease (DRM) on D15 and D35 of treatment, assessed by cytometry immunophenotyping flow (CMF). Patients with <1,000 blasts / mm3 (absolute value) in peripheral blood (SP) at D8 are considered to be good responders. Likewise, they are considered as good responders when minimal residual disease (DRM) in bone marrow (OM) <0.01% of blasts in D15 and D35 of treatment. The aim of this study was to assess whether the relative quantification of leukemic cells (percentage of blasts) in SP at D8 for treatment of ALL patients is associated with DRM at D15, D35, relapse and overall survival (SG). Material and methods: seventy-four patients diagnosed with ALL, from 2014 to 2019, from the oncology reference center in the state of Maranhão were included in this study. Clinical, laboratory and immunophenotypic data were collected and registered in a database for further correlation analysis. In the treatment D8, automated blood count, cytomorphological evaluation and immunophenotyping by CMF were performed to determine the absolute (per mm3) and relative value of blasts in peripheral blood. It was established as a cohort point of the relative value of 5% of blasts in SP for comparative analysis. Overall survival (SG) at 48 months was analyzed using the Kaplan-Meier method and differences between groups were compared using the log-rank test. A p value <0.05 was considered to be statistically significant. Results: 85.1% reached a blast count on day 8 of treatment ≤1,000 / mm3, which corresponds to 63 patients. It was observed that most of the patients (73%) were not good responders to chemotherapy in the D15 of the treatment, who presented DRM> 0.01%. On day 35 or 33 of treatment, 44.6% responded to therapy (negative DRM) and 47.3% did not (DRM> 0.01%). Of the 74 patients analyzed, 22 died (29.7%) and 11 (14.9%) relapsed. The correlation of the percentage of blasts in D8 determined by cytomorphology and CMF was satisfactory (r = 0.66, p<0.001.) There was no association of absolute values (<1,000 blasts / mm3 and ≥ 1,000 blasts / mm3) and relative (<5% blasts and ≥5% blasts), identified both by cytomorphology and CMF, on D8, with DRM on D15, DRM on D35 and relapse. It was observed in the total cohort that it influenced the SG by stratification 1,000 blasts / mm3 and ≥1,000 blasts / mm3 and by the 5% blast cohort point determined only by CMF. SG of 44.4% for <1,000 blasts / mm3 and 73.4% for ≥1,000 blasts / mm3 (p = 0.03). For patients with <5% of blasts at D8, SG was 74.7% and for those with ≥ 5%, SG was 53.3% (p = 0.03). In the group of patients with <1,000 blasts / mm3, it was observed that patients with ≥ 5% of blasts had a lower SG (50.0%) and patients with <5% greater SG (78.9%) (p = 0,01). Conclusion: The relative percentage of blasts determined by CMF should be taken into account in D8, especially in the group of patients considered to be good responders (<1,000 blasts / mm3), where it was observed that the relative value (above 5% of blasts) demonstrated to significantly influence overall survival.